2022
DOI: 10.3390/ijerph191912757
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Emotion Recognition in Young People, Healthy Older Adults, and Patients with Mild Cognitive Impairment

Abstract: Background: The basic discrete emotions, namely, happiness, disgust, anger, fear, surprise, and sadness, are present across different cultures and societies. Facial emotion recognition is crucial in social interactions, but normal and pathological aging seem to affect this ability. The present research aims to identify the differences in the capacity for recognition of the six basic discrete emotions between young and older healthy controls (HOC) and mildly cognitively impaired patients (MCI). Method: The samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Some studies have confirmed that emotion regulation is impaired in MCI (Bora and Yener, 2017;Liu et al, 2022), mainly focusing on negative emotions and that the recognition of positive faces, such as joy, happiness, and hope, is no different from healthy older adults (McCade et al, 2013;Elferink et al, 2015;Barbieri et al, 2022). This seems to suggest that MCI retains the "positive effect. "…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Some studies have confirmed that emotion regulation is impaired in MCI (Bora and Yener, 2017;Liu et al, 2022), mainly focusing on negative emotions and that the recognition of positive faces, such as joy, happiness, and hope, is no different from healthy older adults (McCade et al, 2013;Elferink et al, 2015;Barbieri et al, 2022). This seems to suggest that MCI retains the "positive effect. "…”
Section: Introductionmentioning
confidence: 96%
“…Some studies have confirmed that emotion regulation is impaired in MCI ( Bora and Yener, 2017 ; Liu et al, 2022 ), mainly focusing on negative emotions and that the recognition of positive faces, such as joy, happiness, and hope, is no different from healthy older adults ( McCade et al, 2013 ; Elferink et al, 2015 ; Barbieri et al, 2022 ). This seems to suggest that MCI retains the “positive effect.” In addition, based on scholars’ proposal of the dual competition models, it is known that emotions and cognitions compete with each other, and the process largely depends on attentional capture ( Pessoa, 2009 ).…”
Section: Introductionmentioning
confidence: 98%